European Stroke Organisation Guideline on Reversal of Oral Anticoagulants in Acute Intracerebral Haemorrhage. (December 2019) - Christensen, Hanne; Cordonnier, Charlotte; Kõrv, Janika; Lal, Avtar; Ovesen, Christian; Purrucker, Jan C; Toni, Danilo; Steiner, Thorsten
Abstract: The aim of the present European Stroke Organisation guideline document is to provide clinically useful evidence-based recommendation on reversal of anticoagulant activity VKA (warfarin, phenprocoumon and acenocoumarol), direct factor II (thrombin) inhibitors (dabigatran etexilat) and factor-Xa-inhibitors (apixaban, edoxaban and rivaroxaban) in patients with acute intracerebral haemorrhage. The guideline was prepared following the Standard Operational Procedure for a European Stroke Organisation guideline document and according to GRADE methodology. As a basic principle, we defined use of oral anticoagulation pragmatically: oral anticoagulation use is assumed by positive medical history unless relevant anticoagulant activity is regarded unlikely by medical history or has been ruled out by laboratory testing. Overall, we strongly recommend using prothrombin complex over no treatment and fresh-frozen plasma in patients on VKA plus vitamin K. We further strongly recommend using idarucizumab in patients on dabigatran and make a recommendation for andexanet alfa in patients on rivaroxaban and apixaban over no treatment. We make a weak recommendation on using high-dose prothrombin complex concentrate (50 IU/kg) for all patients taking edoxaban and for patients on rivaroxaban or apixaban in case andexanet alfa is not available. We recommend against using tranexamic acid and rFVIIa, outside of trials. The presented treatment recommendations aim to normalise coagulation, there is no or only indirect data on effects on functional outcome or mortality, and only little data from randomised controlled trials.